Distinguishing Gender Identity From Biological Sex in Dermatologic Health Care: Methods, Harms, and Paths Forward - Noah N Nigro; Neal Chandnani; Athena Doshi; Alexa Fritsch; Nathaniel A Marroquin; Morgan Zueger; Torunn E Sivesind; Robert Dellavalle; Cory Dunnick (JMIR Publications, 2023)
Accurate assessment of gender identity and biological sex in dermatology research is crucial since their conflation or poor demarcation undermines patient respect and study accuracy. Clearer guidance is needed for health care researchers, particularly in light of the notable disparities in skin disease rates, skincare practices, literature representation, and the persistent underrepresentation of transgender and nonbinary patients.